Performance pay and applicant screening - Uwe Jirjahn; Jens Mohrenweiser (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2015)
Using German establishment data, we show that the relationship between performance pay and intensity of applicant screening depends on the nature of production. In establishments with increased multitasking, performance pay is associated with a greater intensity of applicant screening. In establishments without increased multitasking, it is associated with a reduced intensity. The findings fit the hypothesis that performance pay induces a positive self-sorting of employees if jobs are less multifaceted. In this case, employers using performance pay need no intense applicant screening to ensure a high quality of matches between workers and jobs. However, if jobs are more multifaceted, performance pay can entail problems of adverse selfsorting. In order to mitigate or overcome these problems, employers tying pay to performance screen applicants more intensely.
Keywords: J33; J60; M51; M52; 330; performance pay; multitasking; self-sorting; applicant screening; non-managerial employees; managerial employees